Scalp induction rate responses to cytokinins on proliferating shoot-tips of banana cultivars (Musa spp.) - Bidabadi, Siamak Shirani; Meon, Sariah; Wahab, Zakaria; Mahmood, Maziah (Science Publications, 2010)
Problem statement: The effect of cytokinins on scalp induction from in vitro propagating shoot tips of different banana (Musa spp. AAA and AAB) cultivars was studied. Approach: Proliferation rate increased with an increasing concentration of Benzyl Amino Purine(BAP) up to 22.2 μM while, lower level of BAP (11.1 μM) increased scalp induction. Results: Kinetin induced a lower number of shoots than that obtained with similar levels of BAP and caused an increase in scalp induction rate at higher concentration (22.2 μM). Shoot proliferation in ‘Rastali’(AAB),‘Berangan Intan’ and ‘Berangan’(AAA) significantly increased with increasing Thidiazuron (TDZ) concentration from 3.17, 2.17 and 3.33 shoots at 0.5 μM to 14.17, 6.22 and 6.17 shoots at 5 μM respectively, as concentrations above 5 μM for all cultivars were inhibitor. Conclusion/Recommendations: The highest ratio of scalp formation (8.89) was recorded in ‘Rastali’ at the highest concentration of TDZ (7.5 μM), but in ‘Berangan Intan’ and ‘Berangan’ (AAA) TDZ increased scalp induction rate from 0.00 and 0.43 at 0.5 μM to 4.22 and 2.67 at 5 μM respectively before falling to 2.11 for both at 7.5 μM. BAP at 22.2 μM was considered optimal for shoot proliferation as well as shoot elongation from excised scalps of banana cultivars.